ROLE OF ALPHA-1 BLOCKER IN EXPULSION OF STONE FRAGMENTS AFTER EXTRACORPOREAL SHOCK WAVE LITHOTRIPSY FOR RENAL STONES - Pirzada, Abdul Jabbar; Anwar, Adeel; Javed, Atif; Memon, Imran; Mohammad, Ariz (Journal of Ayub Medical College Abbottabad, 2011)
Background: Renal stone disease is a significant and worldwide health problem. Recent advances in stone management have allowed kidney stones to be treated using extracorporeal shock wave lithotripsy (ESWL), uretero-renoscopy (URS), and percutaneous nephrostolithotomy (PCNL). Recently, medical expulsion therapy (MET) has been investigated as a supplement to observation in an effort to improve spontaneous stone passage rates. Patients and Methods: This study was a randomized, controlled, prospective study to determine whether the administration of Alpha-1- adrenergic receptor antagonists as an adjunctive medical therapy, increases the efficacy of ESWL to treat renal stones. Sixty patients with renal stones of 0.5-1.5 Cm in size (average size 1.2 Cm) were included in this study underwent ESWL followed by administration of Alpha-1-adrenergic receptor antagonists at department of Urology Liaquat National Hospital Karachi from Feb 2008 to Sept 2008. This was a comparative study and patients were divided into two groups. In group A patients received conventional treatment Diclofenac sodium, Anti Spasmodic (Drotverine HCl) as required and Proton Pump inhibitor (Omeprazole 20 mg) once daily after shock wave lithotripsy. In group B patients received alpha-1 blocker, Alfuzosin HCl 5 mg twice daily in addition to conventional treatment. All patients were instructed to drink a minimum of 2 litres water daily. Ultrasound guided Dornier Alpha Impact Lithotripter was utilised for shock wave lithotripsy. Results: Of the 60 patients, 76.7% of those receiving Alfuzosin and 46.7% of controls had achieved clinical success at 1 month (p=0.01). The mean cumulative diclofenac dose was 485 mg per patient in the Alfuzosin group and 768 mg per patient in the control group (p=0.002). This difference was statistically significant. Conclusion: Alfuzosin therapy as an adjunctive medical therapy after ESWL is more effective than lithotripsy alone for the treatment of patients with large renal stones and is equally safe. It increases the expulsion rates of stones, decreases time to expulsion, and decreases need for analgesia during stone passage. Keywords: Alpha-blockers, Ureteral stones, Kidney stones, ESWL